INDIKASI TERJADINYA MANAJEMEN LABA DI SEKITAR AKTIVITAS PENERBITAN RIGHT ISSUE - Diyah, Diyah (potensio, 2014)
This research aimed to examine the accrual-based and real activity earnings management around the activity of issuing rights issue, and the differences in the amount of earnings management by the company between the period before and after the issuance of rights issue. In this research, accrual-based earnings management measured by discretionary accruals using the Modified Jones Model. While the real earnings management is measured by three variables of real activity, which is through the cash flow operations, production costs and discretionary costs. The results of this research showed that the company issuing right issue did accrual-based and real earnings management with overproduction and discretionary cost reduction techniques around the issuance of right issue activity. In addition, this study show that the amount of earnings management in the period before and after the issuance of right issue have differences. Accrual earnings management after the issuance of right issue was larger than the previous period and abnormal discretionary costs prior to the issuance of right issue was lower than that after issuance.Keywords: Earnings Management, Accrual-Based Earnings Management, Real Earnings Management, Right Issue